2015
DOI: 10.1242/jeb.128843
|View full text |Cite
|
Sign up to set email alerts
|

Temperature experienced during incubation affects antioxidant capacity but not oxidative damage in hatchling red-eared slider turtles (Trachemys scripta elegans)

Abstract: Our understanding of how oxidative stress resistance phenotypes are affected by the developmental environment is limited. One component of the developmental environment, which is likely central to early life oxidative stress among ectothermic and oviparous species, is that of temperature. We investigated how incubation temperature manipulations affect oxidative damage and total antioxidant capacity (TAC) in red-eared slider turtle (Trachemys scripta elegans) hatchlings. First, to determine whether temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Alternatively, the site differences may be due to the relatively small spread of ages in the cool highland data compared to the warm lowland data. The difference in telomere length between sites could also reflect some degree of local adaptation in capacity to cope with oxidative stress [72]. Highland populations experience longer average brumation periods than warm lowland populations, meaning a longer time at low body temperatures and low metabolic rates associated with a decrease in cellular turnover and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the site differences may be due to the relatively small spread of ages in the cool highland data compared to the warm lowland data. The difference in telomere length between sites could also reflect some degree of local adaptation in capacity to cope with oxidative stress [72]. Highland populations experience longer average brumation periods than warm lowland populations, meaning a longer time at low body temperatures and low metabolic rates associated with a decrease in cellular turnover and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…2). Prior work with reptiles has demonstrated that hotter temperatures do not inherently result in oxidative damage (Treidel et al 2016), and prolonged exposure to warmer temperatures in fish can actually decrease oxidative damage (Enzor and Place 2014). Recent evaluation of the dynamics at the mitochondrial membrane indicates that increased metabolic rate (e.g., due to increased temperature) may actually reduce-rather than increase-the production of reactive oxygen species associated with oxidative damage (Speakman and Garratt 2014;Salin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental rate in some reptiles accelerates with temperature, as does mitochondrial respiration (Sun et al ., ), so it is feasible that that ROS could accumulate more quickly at a higher temperature, activating responses to oxidative stress. Further, antioxidant capacity in embryos varies in response to incubation temperature in a TSD turtle (red‐eared slider, Trachemys scripta elegans ), indicating that metabolic rate and ROS accumulation vary with temperature (Treidel et al ., ). Additionally, yolk deposition of antioxidants is greater in birds with shorter developmental periods (Deeming et al ., ), suggesting that even in a homeothermic taxon, faster development results in greater oxidative stress.…”
Section: Calcium and Redox Regulation In The Cellmentioning
confidence: 97%
“…They are typically rapidly dismuted through a series of antioxidant reactions (Camello‐Almaraz et al ., ; Yan et al ., ; Hamanaka & Chandel, ). If ROS production outweighs the antioxidant capacity of the cell, the redox environment can be altered to an oxidizing state (Treidel, Carter & Bowden, ). However, at physiologically moderate levels (eustress), ROS possess vital cellular signalling roles in growth, homeostasis, reproduction, and programmed apoptosis (Covarrubias et al ., ; Dowling & Simmons, ; Sies, Berndt & Jones, ).…”
Section: Calcium and Redox Regulation In The Cellmentioning
confidence: 99%